LEGAL REVIEW OF COPYRIGHT AS CREDIT COLLATERAL IN THE GUARANTEE LEGAL SYSTEM IN INDONESIA - Asep Hidayat; Tofik Yanuar Chandra; Jelly Nassery (DE'RECHTSSTAAT, 2022)
Collateral  is an important element in the credit agreement in order to give confidence to the creditor that with the guarantee from the debtor he can repay the loan. UU no. 28 of 2014 concerning Copyright states that copyright as a movable object can be used as a fiduciary guarantee, because it has economic value. The research method used is a normative juridical legal research method by taking an analytical approach to the legislation. The results of this study indicate that objects that can be pledged as collateral are objects that meet certain conditions. As one of the material rights, copyright contains two rights, in addition to economic rights that can provide benefits in the form of royalties, there are also moral rights that are always attached to the owner. Economic rights can be transferred or transferred to other people (transferable), so that other people as recipients of the transfer of rights also get economic benefits.